Telaah Nilai-Nilai Pendidikan Antikorupsi dalam Pendidikan Agama Islam di Madrasah Ibtidaiyah - Faizatul Widat (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Abstract: This study is to find out the implementation of anti-corruption education values in Madrasah Ibtidaiyah, as the implementation of anti-corruption education values in Islamic religious education is useful to eliminate the nature of corrupt behaviour for students in Madrasah Ibtidaiyah. The focus of this study: (a) how the implementation of anti-corruption education values in Islamic religious education of students of Madrasah Ibtidaiyah, (b) whether the values of anti-corruption education in Islamic religious education are beneficial to eliminate the nature and behaviour of Madrasah Ibtidaiyah students. This study uses qualitative data, which is a study that presents data with integration and internalization methods, this approach aims to understand phenomena that occur through a holistic picture and increase in-depth understanding of the values of anti-corruption education in this research. The results of this study indicate that: (a) students have early understanding of anti-corruption education, (b) students can prevent themselves from doing it, (c) students are able to prevent others from committing acts of corruption, (d) students are able to detect the existence of criminal acts of corruption.